2021
DOI: 10.1093/ajcp/aqab014
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Diagnostic Miscommunication in Pathology

Abstract: Objectives The pathology report serves as a crucial communication tool among a number of stakeholders. It can sometimes be challenging to understand. A communication barrier exists among pathologists, other clinicians, and patients when interpreting the pathology report, leaving both clinicians and patients less empowered when making treatment decisions. Miscommunication can lead to delays in treatment or other costly medical interventions. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…An audit of pathology reports showed that if a sample size of 50 gives a sample error rate of 2% there is a 95% probability that the true error rate is up to 10.9% [16]. Moreover, up to one-third of clinicians do not always understand pathology reports, which causes misinterpretation and uncertainty in clinical diagnosis [17]. DL approaches applied to histopathological slide images aim to significantly speed up the diagnosis and simplify their implementation into clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…An audit of pathology reports showed that if a sample size of 50 gives a sample error rate of 2% there is a 95% probability that the true error rate is up to 10.9% [16]. Moreover, up to one-third of clinicians do not always understand pathology reports, which causes misinterpretation and uncertainty in clinical diagnosis [17]. DL approaches applied to histopathological slide images aim to significantly speed up the diagnosis and simplify their implementation into clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…The term “knowledge translation” has been utilized in oncology and pathology and is defined as the method for closing the gaps between knowledge and practice 10 . It also refers to the application of knowledge in clinical practice among different groups within the health care team such as providers, patients, and other health care professionals 11 . In surgical pathology, “knowledge translation” of the report, and the content thereof, is extremely important 11 .…”
Section: Discussionmentioning
confidence: 99%
“…We have presented a case as an example of how uncertainty phrases can cause confusion as well as additional work and cost. With up to one-third of clinicians not understanding the pathology report, it is vital to emphasize the importance of clear and effective “knowledge translation” of the final diagnosis 11 . There have been proposed systems as to how to tackle uncertainty, including a standardized scheme where each phrase is given a number-based (ie, “50%–79%”) level of uncertainty 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Для правильной постановки диагноза и назначения необходимого лечения требуется скоординированная работа лечащего врача и врачапатологоанатома. Однако их взаимодействие может быть ограничено как различиями в терминологии, классификациях, устоявшихся только среди патологоанатомов формулировках, используемых при написании заключения, так и отсутствии доступа патологоанатома к истории болезни и иной медицинской документации пациента [14]. Исследование Barbieri A.L.…”
Section: выставление показаний для патоморфологического исследованияunclassified